The Economics of Palestine: economic policy and institutional reform for a viable Palestinian State - Kanafani, Nu'man; Cobham, David (London Routledge, 2004)
"​This book aims to set the intense political debates on one side in order to do some serious economic analysis. It assumes that a sovereign independent Palestinian state comes into existence in the West Bank and Gaza Strip, and proceeds to examine the economic policies and institutional reforms which would be appropriate for it. Key recommendations are that such a state should: * adopt a non-discriminatory trade regime ..." https://www.tau.ac.il/~razin/palestinianeconomy.pdf
​Introduction / David Cobham and Nu’man Kanafani -- 2 The choice of trade regime depends on multiple other factors / Sébastien Dessus and Elizabeth Ruppert Bulmer 3 Alternative currency arrangements / David Cobham 4 Budgetary and fiscal policy / Christopher Adam, David Cobham and Nu’man Kanafani 5 The role of the financial sector / Osama Hamed 6 Company law and corporate governance / Clare Woodcraft and Khaled Islaih 7 Structuring a Pension Scheme for a Future Palestinian State / Edward A. Sayre and Jennifer C. Olmsted 8 Strategies for economic development, the role of Gaza, and the future of the refugee camps/Chris Jensen-Butler and Eduardo Anselmo de Castro 9 Foreign aid strategy/ Anne Le More 10 Absorbing returnees in a viable Palestinian state: a forward looking macroeconomic perspective/Arie Arnon and Nu’man Kanafani 11 Incomplete contracts, the port of Gaza, and the case for economic sovereignty/Arie Arnon, Avia Spivak and Oren Sussman
Includes bibliographical references and index
Keywords: Economic conditions; ECONOMIC CONDITIONS; ECONOMIC POLICY; ECONOMIC ANALYSIS; PALESTINE